Soft Power - Panayides, Angelos (My University, 2023)
Cyprus Design & Advertising Awards The Pygmalion Awards exists to inspire, educate and unite. The best of Cyprus Design & Advertising, brings together the published local work to award the best work of the year and set the highest standards of creative excellence in Cyprus. The challenge for our jurors is to recognise the best work in each category and award it a Gold, Silver or Bronze Pygmalion accordingly, that will then give it the chance to compete at the ADC*E Awards against the best work in Europe. This is a wonderful opportunity for industry professionals to come together and highlight creativity.
EIPF4
Keywords: PYGMALION AWARDS 23; PRAISE